Applying Improved Bee-Inspired Algorithm for The Vehicle Routing Problem - Oskar SKUBISZ1; Hubert ZARZYCKI1; Marta WINCEWICZ-BOSY1; Dawid EWALD2 (Communications of International Proceedings, 2021)
The article describes the ABC (Artificial Bee Colony) algorithm, which is one of the nature-inspired algorithms. Bee algorithms are a group of algorithms whose operation is modeled on the intelligent behavior of a swarm of bees. This behavior involves searching for food and exchanging information about food abundant locations. The proposed modified ABC algorithm was used to find the optimal solution for the VRP (Vehicle Routing Problem). The improved solution enables the use of additional parameters for vehicles intended to service warehouses, such as: warehouse service costs, maximum range of connection points, probability of lack of connection or probability of out-of-range connection. The solution was implemented in C#. The developed system enables support in planning the optimal route leading between the selected starting point and one of the many warehouses (destination points). A number of experiments were carried out and interesting results were obtained. The authors of the study analyzed the impact of individual standard and additional parameters on the correctness of the results and execution times. The conclusions indicates the potential applications of the presented solutions and the possibilities for further research.
Keywords: Bee algorithm; ABC; vehicle routing problem; routing optimization; swarm intelligence.